Correlation between the atherogenic index of plasma and risk of diabetic retinopathy - Zhang, Yuan; Chen, Guanhua; Jing, Yali (Frontiers in Medicine, 2025)
ObjectiveTo investigate the relationship between the atherogenic index of plasma (AIP) and diabetic retinopathy (DR) in patients with type 2 diabetes mellitus (T2DM).MethodsA total of 584 patients with T2DM were divided into two groups based on whether with DR (non-DR group, n = 382; DR group, n = 202). The association between AIP and DR was assessed by Spearman’s correlation and bivariate/multivariate logistic regression.ResultsThe patients in the DR group showed significantly higher AIP levels than those in the non-DR group (−0.009 ± 0.226 vs. 0.186 ± 0.261, p < 0.001). Compared with those without DR, DR group had higher levels of age, systolic blood pressure (SBP), body mass index (BMI), diabetes duration, triglycerides (TG), blood urea nitrogen (BUN) and creatinine (Cr), while direct bilirubin (DBIL) and high-density lipoprotein cholesterol (HDL-C) were lower (p < 0.05). According to the interquartile range of AIP, the participants were divided into four groups: Q1 (≤−0.130), Q2 (−0.129, 0.048), Q3 (0.049, 0.220), Q4 (≥0.221). After adjusting for age, BMI, SBP, diabetes duration, DBIL, BUN and Cr, the logistic regression model indicated that subjects in Q3 and Q4 still had a remarkably increased risk of DR (Q3: OR, 2.838, 95% CI: 1.268 ~ 7.067; Q4: OR, 4.414, 95% CI: 1.841 ~ 10.097; all p < 0.05). AIP provided an AUC value of 0.697 for retinopathy in patients with T2DM (95% CI: 0.652 ~ 0.741).ConclusionAIP is associated with diabetic retinopathy in patients with T2DM, and AIP may be a potential predictor of DR in patients with T2DM.